Strega Nona - de Paola, Thomas Antony (U.S.A : Aladdin paperbacks, 1975)
When Strega Nona leaves him alone with her magic pasta pot, Big Anthony is determined to show the townspeople how it works.
TR/PS
Keywords: Folklore -- Italy; Children stories